Evaluating the photocatalytic activity of 14.6TiO2–7Na2O–23B2O3-55.4SiO2 (mol.-%) glass based porous catalysts after selective laser sintering and conventional shaping. Issue 22 (15th November 2022) - Kwinda, Tovhowani Innocent; Oberleiter, Bastian; Fischer, Kristina; Thomas, Isabell; Schulze, Agnes; Enke, Dirk; Koppka, Sharon
Abstract: Direct application of TiO2 nanopowder in water remediation is hindered due to sophisticated separation of the photocatalyst. Therefore, alternative partially crystallized porous glass based photocatalysts were prepared on the basis of combined phase separation and partial crystallization of 55.4SiO2 –23B2 O3 –7Na2 O-14.6TiO2 (mol.-%) initial glass composition followed by selective leaching. The advantage of this glass composition is that, 3-D shaping is possible via selective laser sintering technique. Therefore, various macroscopic shapes were fabricated via selective laser sintering and conventional techniques and their resulting properties and photocatalytic activities were compared. Selective laser sintered glasses contain slightly less content of anatase phase due to formation of rutile during sintering process as opposed to conventional glasses. Textural properties are similar in both selective laser sintered and conventional shaped glasses which indicate similar phase separation mechanism and microstructure. In terms of macroscopic shapes, photocatalytic activity increases in the order: monolith < granulate < "macropowder" due to increase in the surface area to volume ratio. The photocatalytic activity is mainly determined by the amount of the anatase phase, thus conventional glasses exhibit slightly higher activity than selective laser sintered glasses. Graphical abstract: Image 1